Ambivalent Childhoods : Speculative Futures and the Psychic Life of the Child - Breslow, Jacob (Book collections on Project MUSE., 2021)
"Explores childhood in relation to blackness, transfeminism, queerness, and deportability to interrogate what "the child" makes possible"--